Taking it personally? The role of personality in strategic crisis management - Hanna Hottenrott; Eline Schoonjans (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Economic crises can have substantial impacts on companies and their stakeholders. The ability of organizations to manage and cope with crises is therefore central to the direction and severity of their impact. We explore an underidentified determinant of strategic crisis management by focusing on the role of decision-makers' non-cognitive and cognitive traits. In a representative sample of 1,408 young companies founded between 2012 and 2019 in Germany, we find that founders' personality impacts the choice of crisis management strategy in the COVID-19 context. Risk-tolerant founders respond with operative innovation rather than retrenchment. Conscientiousness is linked to choosing a perseverance strategy and openness to experience to strategic innovation. More agreeable founders, however, are generally less responsive. Finally, migration experience and education are positively associated with innovative crisis responses. Our results have implications for policymakers and practitioners when designing measures to cope with economic distress.
Keywords: D21; L21; L26; M2; O30; 330; Strategic Crisis Management; Crisis Responses; COVID-19; Founder Personality; Cognitive Traits